Genetic Diversity of Captive and Semi-Wild Orangutan (Pongo spp.) in Malaysia - Yuvarajan, A/L Manivannan (Universiti Malaysia Sarawak (UNIMAS), 2019)
There are two major components in this study, i) taxonomic status and genetic diversity of captive Orangutan in Malaysia and ii) pedigree information of Orangutan in captive and rehabilitation centres in Sarawak. Orangutan is the only great ape that has wild populations outside of Africa, which is in Northern Sumatra and Borneo. Currently there are three species of Orangutan recognized, which are the Sumatran Orangutan (Pongo abelii), Tapanuli Orangutan (Pongo tapanuliensis) and Bornean Orangutan (Pongo pygmaeus). The Bornean Orangutan were further classified into three subspecies which are P. p. pygmaeus, P. p. wurmbii and P. p. morio. Orangutans were listed as critically endangered in wild due to their rapid population decline caused by habitat destructions and hunting. Meanwhile many captive facilities around the world are keeping Orangutans for conservation and tourism purposes. More than 100 Orangutans are kept in various captive and rehabilitation centres in Malaysia. However, its taxonomic status is poorly known by the management. As all the species and subspecies within the genus Pongo are geographically isolated in wild, there must be notable genetic differences among them. These genetic variations should be maintained even in captive facilities. Moreover, taxonomic information of Orangutan could eventually aid in determining its original wild population for its reintroduction. Thus, noninvasive samplings were conducted at various captive and rehabilitation centres in Malaysia to perform a genetic profiling of captive Orangutans. The mitochondrial protein-coding (ND5) and non-coding (Dloop-HVR1) genes used in the phylogenetic analysis has provided substantial taxonomic information of all the captive Orangutans included in this study. There were several species misidentifications recorded in this study along with the noteworthy finding of Pongo tapanuliensis in A’famosa Resort, Malacca where it was previously misidentified as P. abelii. This is the first report of Tapanuli Orangutan in captivity. Besides that, it is also crucial to have the pedigree information of captive Orangutans. This is because unknown pedigree information could lead to inbreeding depression where the loss of unique alleles could be severe. Moreover, parentage misclassifications were reported to be common among captive Orangutans in Sarawak. Therefore, microsatellite genotyping was done using the non-invasive samples of Orangutans from Matang Wildlife Centre and Semenggoh Orangutan Rehabilitation Centre. The results have resolved parentage misclassifications and provided reliable pedigree information as well as accessing their genetic diversity that can help in the proper management of these critically endangered species. This study has highlighted the importance of genetic profiling of captive animals where species identification and pedigree assessment could be accurate.